Study of oxidant and anti-oxidant status in patients with chronic kidney disease - A V. S S. N. Sridhar; P V. L N. Srinivasa Rao; Vishnubhotla Sivakumar; P Satish; P Shalini; M M Suchitra; Vinapamula S Kiranmayi (Journal of Clinical and Scientific Research, 2018)
Background: Chronic kidney disease (CKD) is associated with oxidative stress (OS), which occurs even in early stages of CKD and was shown to further contribute to progression of renal dysfunction and increased cardiovascular risk in CKD patients. Majority of studies have evaluated OS in CKD patients using limited biomarkers. Present study aimed at comprehensive evaluation of oxidant and antioxidant status in CKD patients. Methods: 120 patients diagnosed with CKD who were classified into three groups of 40 each [group-1 (CKD stage1 and 2), group-2 (CKD stage3 and 4) and group-3 (CKD stage 5] based on eGFR and 30 healthy controls were recruited. Malondialdehyde (MDA), protein carbonyls (PC), ferric reducing ability of plasma (FRAP), protein thiols, superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase were measured in all subjects. FRAP was corrected for uric acid (FRAP_UA) and MDA/FRAP_UA ratio was calculated. Score for oxidative stress (SOS) was calculated using the oxidant antioxidant parameters studied. Results: MDA, PC, MDA/FRAP_UA, FRAP and SOS were higher whereas protein thiols, SOD, GPx and catalase were lower in CKD patients than controls. Further, MDA, PC and FRAP and SOS increased progressively and protein thiols, SOD and catalase decreased progressively with increasing renal dysfunction. MDA, PC, FRAP and SOS showed positive correlation with creatinine and negative correlation with eGFR, whereas protein thiols, SOD, and catalase showed positive association with eGFR and negative correlation with creatinine. Conclusions: CKD patients are prone for oxidant injury which increases progressively with worsening renal dysfunction and is associated with degree of renal impairment. Score for oxidative stress helps in comprehensive assessment of oxidative stress in CKD patients.